2013
DOI: 10.1016/j.kjms.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species scavenging activities in a chemiluminescence model and neuroprotection in rat pheochromocytoma cells by astaxanthin, beta‐carotene, and canthaxanthin

Abstract: The objective of this study was to determine chemiluminescence (CL) antioxidant activities and neuroprotective effects of astaxanthin, beta-carotene (β-carotene), and canthaxanthin on undifferentiated rat pheochromocytoma (PC12) cells. We performed three CL antioxidant assays, and the three carotenoids showed varying degrees of antioxidant activity, with astaxanthin exhibiting the highest antioxidant activity than the other two samples. Results of a pyrogallol-luminol assay revealed β-carotene to have higher a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Astaxanthin (at 10 µM) exhibited stronger activity than β-carotene and canthaxanthin in reducing the cytotoxicity induced by Aβ 25-35 (Chang et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Astaxanthin (at 10 µM) exhibited stronger activity than β-carotene and canthaxanthin in reducing the cytotoxicity induced by Aβ 25-35 (Chang et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…In general, canthaxanthin scavenges reactive oxygen species , but canthaxanthin does not seem to scavenge peroxynitrite anion free radicals (ONOO − ) . Geometrical isomerization seems to have an impact in terms of the free radical scavenging activity of canthaxanthin .…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…48 CX is also an antioxidant and may have great potential in the treatment of neurological diseases. It has been found that CX has antioxidant, anti-apoptosis and immunomodulatory activity, [30][31][32]49 but the cell membrane receptors were not identified and the mechanism of these effects were not clear. TMEM16A mediate diverse physiology in cells, which play important roles in nociception, transduction of nerves, contraction of smooth muscle, epithelial Cl − secretion and fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, CX has been shown to have the ability of scavenging free radicals and reactive oxygen species (ROS). 31 Studies have found that excessive production of ROS activates apoptotic signals and causes apoptosis. 32 In this study, we identified CX as a natural TMEM16A activator that has highly efficient, target specific and nontoxic properties, and further explored the putative binding site between CX and TMEM16A using molecular docking and site-directed mutation methods.…”
Section: Introductionmentioning
confidence: 99%